Pembinaan Literasi Budaya Siswa Kelas V Melalui Kegiatan Memasak Makanan Khas Banyuwangi Di SD Negeri 1 Sumberbaru - Trianingsih, Rima; Faridhatussoliha; Eko Subiantoro; Andy Rahman (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2023)
The results of interviews conducted with several respondents from grade V students of SD Negeri 1 Sumberbaru showed that some students still did not know about the original culture of Banyuwangi. This raises anxiety for educational institutions as places of cultural inheritance. Therefore, it is very important to foster cultural literacy at SD Negeri 1 Sumberbaru as an effort to provide access to understanding and learning the original culture of the Osing Tribe of Banyuwangi. The purpose of this community service is to foster cultural literacy of grade V students at SD Negeri 1 Sumberbaru in knowledge and skills towards the cultural heritage of the Osing tribe, the authentic food of Banyuwangi. The methods used in this community service include socialization, digital education, and practice. From the results of fostering cultural literacy of grade V students through cooking authentic Banyuwangi food at SD Negeri 1 Sumberbaru, it can be concluded that the coaching activities have succeeded in providing understanding and experience of authentic Banyuwangi food.